Radical Roots Public History and a Tradition of Social Justice Activism - Meringolo, Denise D. (Amherst College Press, 2021)
While all history has the potential to be political, public history is uniquely so: public historians engage in historical inquiry outside the bubble of scholarly discourse, relying on social networks, political goals, practices, and habits of mind that differ from traditional historians. Radical Roots: Public History and a Tradition of Social Justice Activism theorizes and defines public history as future-focused, committed to the advancement of social justice, and engaged in creating a more inclusive public record. Edited by Denise D. Meringolo and with contributions from the field's leading figures, this groundbreaking collection addresses major topics such as museum practices, oral history, grassroots preservation, and community-based learning. It demonstrates the core practices that have shaped radical public history, how they have been mobilized to promote social justice, and how public historians can facilitate civic discourse in order to promote equality.